2018
DOI: 10.1039/c8cc03350a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of zero-valent iron nanoparticles via laser ablation in a formate ionic liquid under atmospheric conditions

Abstract: Transition metal nanoparticles (NPs) are promising materials for use as catalysts in many processes, although they are easily oxidized under ambient conditions. In this communication, a novel synthetic method is proposed for producing zero-valent iron (Fe) NPs by laser ablation under atmospheric conditions using the reducing properties of a formate-based ionic liquid solvent. The valence state of Fe was confirmed using X-ray absorption near edge structure (XANES) spectroscopy. The Fe NPs adopt a face centered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In addition to chemical reduction of iron salt described above, microwave assisted synthesis ( González‐Arellano et al, 2008 ), decomposition of iron carbonyls ( Vollmer and Janiak, 2011 ), decomposition of {Fe(N[Si(CH 3 ) 3 ] 2 } 2 in the presence of hydrogen ( Dumestre et al, 2004 ), thermal decomposition of Fe-metal organic framework ( Zhang et al, 2016 ), chemical reduction of iron oxides ( Hisano and Saito, 1998 ), vapor phase condensation ( Stefaniuk et al, 2016 ), mechanical treatment ( Ambika et al, 2016 ), method based on micro-organisms ( Ravikumar et al, 2018 ), Laser ablation method ( Okazoe et al, 2018 ) and carbo-thermal method ( Wang et al, 2018 ) have also been reported for fabrication of iron nanoparticles but Fe nanoparticles prepared by these methods have not been reported yet for reduction of Cr(VI). Therefore, discussion on these methods is out of the scope of present review.…”
Section: Synthesis Of Nanoparticles For Cr (Vi) Reductionmentioning
confidence: 99%
“…In addition to chemical reduction of iron salt described above, microwave assisted synthesis ( González‐Arellano et al, 2008 ), decomposition of iron carbonyls ( Vollmer and Janiak, 2011 ), decomposition of {Fe(N[Si(CH 3 ) 3 ] 2 } 2 in the presence of hydrogen ( Dumestre et al, 2004 ), thermal decomposition of Fe-metal organic framework ( Zhang et al, 2016 ), chemical reduction of iron oxides ( Hisano and Saito, 1998 ), vapor phase condensation ( Stefaniuk et al, 2016 ), mechanical treatment ( Ambika et al, 2016 ), method based on micro-organisms ( Ravikumar et al, 2018 ), Laser ablation method ( Okazoe et al, 2018 ) and carbo-thermal method ( Wang et al, 2018 ) have also been reported for fabrication of iron nanoparticles but Fe nanoparticles prepared by these methods have not been reported yet for reduction of Cr(VI). Therefore, discussion on these methods is out of the scope of present review.…”
Section: Synthesis Of Nanoparticles For Cr (Vi) Reductionmentioning
confidence: 99%
“…Irradiation of an iron metal target with a laser pulse locally melts and vaporizes the metal. Hot metal atoms are cooled by the surrounding medium to form metal NPs [41]. Noble gas sputtering is rarely used for ZVI NPs synthesis.…”
Section: The Top-down Synthesismentioning
confidence: 99%
“…Zerovalent iron nanoparticles were reported by Kimura and coworkers, who used 1064 nm, 8 ns pulses to ablate Fe foil immersed in a reducing ionic liquid comprised of tetraoctylphosphonium cations, [[CH 3 (CH 2 ) 7 ] 4 P] + , and formate anions. 381 This way, oxidation of iron was prevented throughout the nanoparticle formation process. More recently, Kautek, Bomati-Miguel, and Lahoz et al prepared zerovalent iron nanoparticles, which were made by irradiation of a bulk Fe disk with 1064 nm, 4−200 nm pulses, while liquid medium, scan rate, pulse energy, and pulse overlap were systematically varied to probe their effect on nanoparticle production yield and polydispersity.…”
Section: Monometallicsmentioning
confidence: 99%